Calcium Lactate addition in Bioconcrete: Effect on Compressive strength and Water penetration - Irwan J.M; Anneza L.H; Othman N.; Faisal Alshalif A.; Zamer M.M.; Teddy T. (MATEC Web of Conferences, 2016)
This paper presents compressive strength and water penetration of bioconcrete with addition of calcium lactate. Bioconcrete has higher engineering concrete properties and durability compared to normal concrete but the natural production of calcium carbonate is limited to the calcium content in cement. Therefore, additional calcium is added as an additional calcium source to study the influence towards compressive strength and water penetration. The bacteria used in this research are Enterococcus faecalis and Bacillus sp. Calcium lactate was added into concrete mix in concentrations of 0.001mol/l, 0.005mol/l and 0.01mol/l of liquid used. The concentration of bacteria added into the mix is by partial replacement of water used in casting, which are 3% for Enterococcus faecalis and 5% for Bacillus sp. Both compressive strength and water penetration test used cubes of 150mm × 150mm × 150mm. The cubes were tested after 28 days. The result of compressive strength for control is 36 MPa while partial replacement of bacteria yields 38.2 MPa for 3% Enterococcus faecalis and 37.0 MPa for 5% Bacillus sp. Calcium lactate with 0.005 mol/L has the best performance with 42.8 MPa for Enterococcus faecalis and 39.6 MPa for Bacillus sp. Whereas for water penetration, the best concentration of calcium lactate which yielded the lowest water penetration is 0.01 mol/l for both Enterococcus faecalis and Bacillus sp which are 8.7 cm and 8 cm respectively. The addition of calcium lactate into bioconcrete is quite promising for improvement of concrete properties and durability.